Cotton in ancient Sudan and Nubia - Elsa Yvanez; Magdalena M. Wozniak (Revue d'ethnoécologie)
Since Pliny the Elder described the “wool-bearing trees” of Aethiopia in his Natural History, the cultivation of cotton has been a well-known aspect of the textile production of ancient Sudan. It was confirmed during the first decades of Sudanese archaeology by the discovery of many cotton textiles found in Meroe and Lower Nubia, and more recently completed by several archaeobotanical studies conducted in the same regions. The aim of this article is to survey the whole span of data pertaining to cotton in ancient Sudan, collecting information from different sources and chronological periods, so as to trace the evolution of cotton production from the Meroitic to the medieval times. New discoveries have led to a regain of interest for textile research in this part of the world, which will help us contextualize cotton cultivation within the wider framework of clothing and social display, as well as textile craft and the organization of the economy. This multi-disciplinary approach will highlight the important role of Sudan and Nubia in the development of cotton production and exchange in the ancient world.